Conservative Management of Ankyloglossia by Diode Laser: A Case Report - Gyawali, Namrata; Sundas, Sunanda; Sah, Barun Kumar; Dhakal, Neha (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Ankyloglossia or tongue-tie is a congenital condition that results when the inferior lingual frenulum is too short and is attached to the tip of the tongue, limiting its normal movements. Ankyloglossia can lead to different problems such as difficulties in breastfeeding, speech impediments, poor oral hygiene, malocclusion, inability to deglutition, thus being an undesired problem in normal life activity. Among various methods of treatment of ankyloglossia, laser-assisted lingual frenotomy is the simplest, safest, and less traumatic with the most promising results. Here, a case of ankyloglossia and its management by frenotomy with diode laser is reported in a four-year-old female child. After performing partial frenectomy (frenotomy) using a diode laser of 980nm there was an immediate tongue protrusion and slight improvement of phonetics of the patient immediately and altogether improved after six months.